Chronic Administration of a Combination of Six Herbs Inhibits the Progression of Hyperglycemia and Decreases Serum Lipids and Aspartate Amino Transferase Activity in Diabetic Rats - Reza Shafiee-Nick; Ahmad Ghorbani; Farzaneh Vafaee Bagheri; Hassan Rakhshandeh (Hindawi Limited, 2012)
The effects of a polyherbal compound, containing six plants (Allium sativum, Cinnamomum zeylanicum, Nigella sativa, Punica granatum, Salvia officinalis and Teucrium polium) were tested on biochemical parameters in streptozotocin-induced diabetic rats. Streptozotocin caused an approximately 3-fold increase in fasting blood sugar level after 2 days. The diabetic control rats showed further increase in blood glucose after 30 days (384 ± 25 mg/dl in day 30 versus 280 ± 12 mg/dl in day 2, P<0.001). Administration of the compound blocked the increase of blood glucose (272 ± 7 and 269 ± 48 mg/dl at day 2 and day 30, respectively). Also, there was significant difference in the level of triglyceride (60 ± 9 versus 158 ± 37 mg/dl, P<0.01), total cholesterol (55 ± 2 versus 97 ± 11 mg/dl, P < 0.01) and aspartate amino transferase activity (75 ± 12 versus 129 ± 18 U/L, P<0.05) between treated rats and diabetic control group. In conclusion, the MSEC inhibited the progression of hyperglycemia and decreased serum lipids and hepatic enzyme activity in diabetic rats. Therefore, it has the potential to be used as a natural product for the management of diabetes.